Lower-Temperature-Ready Renovation: An Approach to Identify the Extent of Renovation Interventions for Lower-Temperature District Heating in Existing Dutch Homes - Prateek Wahi; Thaleia Konstantinou; Martin J. Tenpierik; Henk Visscher (Buildings, 2023)
This study presents an approach to determine the extent of renovation interventions required for existing Dutch dwellings aiming to transition to lower-temperature district heating (DH) systems. The proposed method is applied to a typical intermediate terraced house built before 1945 in the Netherlands, and it consists of two steps: first, assessing the potential of a dwelling to be heated with a lower temperature supply from DH systems and subsequently developing and evaluating alternative renovation solutions if necessary. This study defines a set of criteria for evaluating the readiness of a dwelling for lower-temperature heating (LTH), considering energy efficiency and thermal comfort as non-compensatory criteria. The application of the approach reveals that the case study dwelling is presently unsuitable for a medium-temperature (70/50 °C) and low-temperature (55/35 °C) supply compared to a high-temperature supply (90/70 °C), thus requiring energy renovations. Furthermore, this study indicates that moderate intervention levels are required for the dwelling to be lower-temperature-ready in both supply temperature goals. These interventions include strategies and measures that upgrade the building envelope to the minimum insulation levels stipulated by the Dutch Building Decree, improve airtightness, and replace existing radiators with low-temperature radiators. By systematically narrowing down renovation options, this approach aids in simplifying the decision-making process for selecting renovations for heating dwellings with LTH through DH systems, which could reduce stakeholders’ decision paralysis.